A Preliminary Study of The Javan Leopard Behaviour in Meru Betiri National Park - Kholiq, Nur; Sucipto, Adi (Life Science and Biotechnology, 2024)
Meru Betiri National Park (MBNP, 526km2), is one of only three protected areas in east Java that can support a viable Javan leopard population. The Javan leopard has become a priority for management following the extinction of the Javan tiger. Therefore, it is important to know how the Javan Leopard behaves to improve species management. We conducted a field study using camera traps to determine the daily behavior of the Javan leopard in MBNP. A monitoring site was established with 73 stations, with a density of one station per 0.5 x 0.5 km grid cell, providing different but comparable densities and spatial coverage. The results indicate that the Javan leopard displays 9 daily behaviors including walking, observing, standing, cheek rubbing, scraping, urine spraying, claw marking, parenting, vocalizing, and others. Each behavior was observed with a relative frequency of walking (63.25%), observing (14.53%), standing (7.69%), cheek rubbing (5.98%), scraping (4.27%), urine spraying (1.71%), claw marking (0.85%), parenting (0.85%) and vocalizing (0.85%). An analysis of the time spent on each behavior revealed their proportion as follows: walking (382 s, 49.29%), watching (208 s, 26.84%), standing (66 s, 8.52%), cheek rubbing (27 s, 3.48%), scraping (57 s, 7.35%), urine spraying (17 s, 2.19%), vocalizing (9 s, 1.16%), claw marking (4 s, 0.52%) and parenting (5 s, 0.65%).